Ecosystem of Technological Business: Methods of Analysis and Development Factors - Hofmeister, G; Mukhtarova, K; Abdykalikova, M; Yerimpasheva, A; Abikenov, A (Farabi Journal of Social Sciences, 2019)
The study covers a challenge of innovative entrepreneurship as a key institutional factor for developing the appropriate ecological system. The purpose of the paper is to formulate fundamental theoretical and practical provisions of a research, which largely focus on the concept of technological entrepreneurship ecosystem. Such factors as a transfer of technologies to ensure a stable model of an innovation and business ecosystem in conditions of a high level of risk and uncertainty in external environment become important internationally. The study provides formulation of the concept of economic ecosystem, basic principles and factors of its functioning. The main findings of the study are due to the fact that the sources of the innovation-entrepreneurial ecosystem’s growth are not only the internal potential of the managerial system, but also external factors of development. External factors include a proactive innovation policy at the regional level with support of science-intensive manufactures, interregional and inter-sectoral economic relations and the ecosystem’s ability to get integrated into the international economic space. Key words: innovative ventures, innovations, innovative ecosystem, sustainable development system, transfer of technologies, adaptive institutional environment, ecosystem of technological entrepreneurship, industrial technological park, innovative corridor, game theory, optimal resource allocation, system compromise.